An electrochemical sensor for the detection of pesticides based on the hybrid of manganese phthalocyanine and polyaniline - KOCA, ATIF (ELSEVIER SCIENCE SA, 2019)
A mimic enzymeless electrochemical sensor (M-Eless-ES) based on the terminal alkynyl substituted manganese phthalocyanine (MnPc-TA) and 4-azido polyaniline (N-3-PANI) hybrid was constructed and tested as a selective and sensitive pesticide sensor. A new electrode modification technique, solid state electropolymerization of a film, was developed for the preparation of ITO/MnPc-TA/N-3-PANI electrode as M-Eless-ES for the first time in this study. During construction of ITO/MnPc-TA/N(3-)PANI electrode, MnPc-TA was firstly deposited on indium tin oxide coated glass substrate (ITO) with Langmuir Blodgett (LB) technique. Then 4-azidoaniline (N-3-ANI) was bonded to the terminal alkynyl substituents of MnPc-TA (ITO/MnPc-TA/N-3-ANI) with click chemistry (CC) and finally ANI groups of the solid MnPc-TA/N-3-ANI hybrid film was electropolymerized on ITO surface to form ITO/MnPc-TA/N-3-PANI electrode. The modified electrode was characterized with square wave voltammetry (SWV), X-ray diffraction (XRD), scanning electron microscope (SEM), and fourier transform infrared (FT-IR). Finally, ITO/MnPc-TA/N-3-PANI electrode was tested as potential M-Eless-ES for the fenitrothion, eserine, and diazinon via SWV technique. Different voltammetric responses were observed for each pesticide. Observation of a new redox peak due to the interaction of the electrode with the fenitrothion indicated its distinct selectivity for this pesticide. The limit of detection (LOD) (0.049 mu mol dm(-3) for fenitrothion, 0.088 mu mol dm(-3) for eserine and 0.062 mu mol dm(-3) for diazinon), wide linear ranges, and especially higher selectivity were observed with ITO/MnPc-TA/N-3-PANI which are the basic requirements for the practical applications for the pesticide sensing. Reproducibility, easy of construction, and stability of the electrode are other superior advantages. As a real sample application, ITO/MnPc-TA/N-3-PANI sensor was successfully employed for determining the fenitrothion residue in rosehip sample.
Keywords: Langmuir Blodgett; Electropolymerization; Click chemistry; Pesticide sensor; Manganese phthalocyanine; Polyaniline; LANGMUIR-BLODGETT-FILMS; REDUCED GRAPHENE OXIDE; ORGANOPHOSPHORUS PESTICIDES; CLICK ELECTROCHEMISTRY; METAL; BIOSENSORS; WATER; IMMOBILIZATION; FENITROTHION; PEROXIDASE